2019
DOI: 10.1111/vsu.13245
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of 119 miniature‐ and toy‐breed dogs with 140 distal radial and ulnar fractures repaired with free‐form multiplanar type II external skeletal fixation

Abstract: Objective: To report the clinical outcomes of miniature-and toy-breed dogs with primary and previously treated distal radial and ulnar fractures (RUF) treated with a free-form multiplanar type II external skeletal fixation (ESF). Study design: Retrospective study. Animals: One hundred nineteen dogs with 140 distal RUF.Methods: Medical records (2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017) were reviewed for dogs weighing up to 7 kg that had been treated for distal RUF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Radius/Ulna fractures in toy breeds are challenging; various different stabilization methods such as miniature circular external fixator, paraosseous clamp-cerclage, mini locking plate and free-form external fixators were reported for their management (Aikawa et al, 2019;Bierens et al, 2017;Kang et al, 2016;Manchi et al, 2017). Despite having a high incidence of complications for R/U fractures (Lappin et al, 1983), external coaptation is the most widely available and cheapest option.…”
Section: Discussionmentioning
confidence: 99%
“…Radius/Ulna fractures in toy breeds are challenging; various different stabilization methods such as miniature circular external fixator, paraosseous clamp-cerclage, mini locking plate and free-form external fixators were reported for their management (Aikawa et al, 2019;Bierens et al, 2017;Kang et al, 2016;Manchi et al, 2017). Despite having a high incidence of complications for R/U fractures (Lappin et al, 1983), external coaptation is the most widely available and cheapest option.…”
Section: Discussionmentioning
confidence: 99%
“…These epidemiological features were consistent with previous studies on small animal orthopaedic surgery. 1,20,21 Approximately, 3% of major complications require postoperative revision using CP systems. 20 Furthermore, a retrospective study using locking compression plates reported that 9% of the complications were implant-related complications.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of techniques exist for the fixation of these fractures. External skeletal fixation can be successfully used (Aikawa et al 2019). However, plate and screw fixation is the most common method of fixation (Gibert et al 2015).…”
Section: Introductionmentioning
confidence: 99%